Role of innovation in pharmaceutical regulation: A proposal for principles to evaluate EU General Pharmaceutical Legislation from the innovator perspective. Issue 5 (May 2023) - Heikkinen, Inkatuuli; Eskola, Sini; Acha, Virginia; Morrison, Alan; Walker, Chris; Weil, Catherine; Bril, Antoine; Wegner, Max; Metcalfe, Thomas; Chibout, Salah-Dine; Chlebus, Magda
Highlights: Pharmaceutical legislation is an important modulator of the pharmaceutical innovation system. The legislation has evolved in the past 20 years into a complex framework. Evaluation principles proposed by R&D leaders facilitate help balancing the scientific opportunity with costs and benefits. The principles are intended for the EU Pharmaceutical Legislation but is suitable for global use for new regulatory policies. Abstract : Because the EU General Pharmaceutical Legislation is under review, the EFPIA Innovation Board developed evaluation principles for the policy proposals and key considerations on how the regulatory framework can support innovation while ensuring only safe, efficacious and quality medicines are authorized. The evaluation principles are anchored on actions to promote: agile adoption of new methodologies with soft law tools; continued emphasis on regulatory science to inform policies; a cost/benefit assessment of the new regulation to ensure they have an overall positive impact; and mitigation of any negative externalities or unintended effects for any type of innovation or products. The evaluation principles are intended to guide the impact assessment of the pharmaceutical legislation in the EU but the principles can be applied globally.